In pursuit of answers to difficult questions: A long story narrated by two journals of the Jewish community, La Boz de Oriente and La Boz de Türkiye - Kayır, Gül Banu. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2017., 2017)
This thesis examines the solutions that the Jewish Community in Turkey came up with in response to growing problems that developed in the period of the 1930s and 40s. Spreading nationalism, the ideal of homogenous state and sim-ultaneously increasing anti-Semitism were among these vital, rapidly devel-oping issues the effects of which were inevitably felt by Jewish communities around the world, including the Jews in Turkey. The work focuses on two spe-cific journals of the community, La Boz de Oriente (1931-1939) and La Boz de Türkiye (1939-1949), to determine the process of thought that led to a partic-ular solution regarding these suffocating problems. The thesis studies the issue of Palestine, the process of establishing a national state and the creation of a national history as parts of said solution. To understand the particular way that the answer was formed, the study examines articles published in the jour-nals over the years and select ones that construe a meaningful whole. Conse-quently, with the help of the community’s own publications, this study inter-prets the endeavors of the Jewish minority in Turkey in subjects of creating a solution to the critical problems and emancipation process.
Keywords: Jews -- Turkey.; Jews -- Turkey -- Newspapers.